Novel IS26-mediated hybrid plasmid harbouring tet(X4) in Escherichia coli. (June 2020) - Du, Pengcheng; Liu, Dejun; Song, Huangwei; Zhang, Pei; Li, Ruichao; Fu, Yulin; Liu, Xiao; Jia, Jinli; Li, Xiaodi; Fanning, Séamus; Wang, Yang; Bai, Li; et al.
Highlights: The tet (X4)-bearing plasmid of a tigecycline resistant E. coli could be transferred. Two plasmid profiles have been identified in the tet (X4) positive transconjugants. A new plasmid was formed by fusion of two plasmids via IS 26 homologous recombination. The non-self-transferable tet (X4)-bearing plasmid might transfer by co-integration. Abstract: Objectives: As the spread of antimicrobial resistance genes becomes an increasing global threat, improved understanding of genetic structure and transferability of the resistant plasmids becomes more critical. The newly description of several plasmid-mediated tet (X) variant genes, tet (X3), tet (X4) and tet (X5), poses a considerable risk for public health. This study aimed to investigate the recombination event that occurred during the conjugation process of a tet (X4)-bearing plasmid. Methods: A Tet(X4)-producing Escherichia coli isolate, 2019XSD11, was subjected to susceptibility testing, S1-PFGE and whole genome sequencing. The genetic features of plasmids and the recombination event were analysed by sequence comparison and annotation. We performed electrotransformation assay to further test the transferability of the tet (X4)-bearing plasmid. Results: A novel type of fusion tet (X4)-bearing plasmid was discovered from the transconjugant, plasmid p2019XSD11-TC2-284 (∼280 kbp). The sequence of this plasmid consisted of a hybrid episome of two plasmids p2019XSD11-190 (∼190 kbp) harbouring tet (X4) and p2019XSD11-92 (∼92 kbp) harbouring bla CTX-M-55 originated from 2019XSD11. The two plasmids were concatenated by IS 26 elements. Analyses of the genetic constitution of the plasmids essential for transmission showed the plasmid p2019XSD11-190 lacked an intact type IV secretion system. Beyond this, the origin of transfer region and relaxase genes in plasmid p2019XSD11-190 had no sequence similarity with those in plasmid p2019XSD11-92. Conclusions: The fusion of the two plasmids probably formed through IS 26 homologous recombination. Such recombination events presumably play an important role in the dissemination of the tet (X4). Molecular surveillance of tet (X) variant genes and genetic structures warrants further investigation to evaluate the underlying public health risk.